Factors contributing to the prevalence of Malaria among Children under five years attending Health Care at Logoba Health Center III, Moyo District . A Cross- sectional Study. - Edebuga, Emmanuel (Student's Journal of Health Research Africa, 2022)
Background: Malaria is an urgent public health priority, its costs of treatment trap families in a cycle of illness, suffering, and poverty, total funding for malaria control and elimination reached an estimated US$ 3billion, and contributions from the government of endemic countries amounted to US$ 900million, representing 31% of total funding (UNICEF, 2019). Methodology: The study design used was a descriptive cross-sectional study design using quantitative data that involved a sample size of 100 caretakers of 100 children below the age of five who attended health care at Logoba HCIII. A simple random sampling method allowed data to be collected on the prevalence of malaria and factors contributing to the Prevalence of Malaria simultaneously from 20th December 2021 to 07th January 2022. Result: The prevalence of malaria was high (35%) and the factors that were significant for the prevalence of malaria included; the caregiver’s knowledge of signs and symptoms like loss of appetite and loss of energy 01%, Socio-economic factors which were contributed by farming and farming related activities, 75% and environmental factor about the presence of garbage heaps 56%. Conclusion: In conclusion, the prevalence of malaria was high at 35% and it was contributed to caregiver’s knowledge about signs and symptoms of malaria, farming and related farming activities like water channels across the garden and farming near home, and garbage heaps around the homes. Recommendation: The study recommended more studies to be done in different areas and regions in the line, an effort to know and understand all signs and symptoms of malaria which are serious signs of severe malaria, sensitization by concerned authorities on how to avoid heap around the household as this is another suitable breeding sites for mosquitoes and sensitization by concerned authorities on safe farming and farm-related activities free for mosquitoes to hide and breed.